Sexual hallucinations: Under-reported yet distressing symptom of schizophrenia – A case series - Koushik Das; Sagarika Ray (Telangana Journal of Psychiatry, 2025)
Sexual hallucination is one of the distressful psychotic symptoms experienced across a variety of psychiatric conditions such as schizophrenia, borderline personality disorder, posttraumatic stress disorder, sedative use, narcolepsy, and night terror, as well as in other conditions like epilepsy. Hence, ruling out organicity is a must in these cases. Among all psychiatric conditions, it is most commonly seen in Schizophrenia. It can be experienced in various modalities such as auditory, visual, olfactory, gustatory, somatic, and tactile. Such symptoms are often missed due to the patient’s feeling of embarrassment as well as the clinician’s indifference to elicit such psychopathology. However, these may form part of residual symptoms in Schizophrenia, which may increase the burden of disability and, therefore, contribute to its chronic, unremitting course. Such symptoms can be attributed to the dopamine rush in the mesolimbic pathway, and thus, antipsychotic drugs are the treatment of choice. Usually, most cases are found to be associated with a history of childhood sexual trauma, which needs to be addressed for focused psychotherapy. In this article, we have described three cases of Schizophrenia who presented with sexual hallucinations in the absence of any comorbid medical or psychiatric illness and showed response to various dosages of Olanzapine. Two of them had complete remission of sexual hallucinations, and one had near-complete resolution. All three patients returned to their normal functioning during treatment with a variable period of treatment with olanzapine and/or psychotherapy.